Providing an entrepreneurial marketing model based on teamwork with an emphasis on start-up companies - Parastoo Bafghi; Mahmoud Ahmadi Sharif; Sina Nematizadeh (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of the current research is to present an entrepreneurial marketing model based on teamwork with an emphasis on start-up companies. The research method is applicable according to its purpose, and qualitative in terms of its implementation. The statistical population consists of 15 experts who are academic professors in the field of marketing management, and managers in the marketing and sales industry, who were selected by targeted non-probability sampling. Thematic analysis method and MAXQDA software were used for data analysis, and MICMAC software was used for effective and effected between variables. The results showed that 5 comprehensive themes and 13 organized themes and 87 basic codes were identified and extracted from the theme analysis method, and then using interpretative structural modeling, the identified indicators were leveled; and the results showed that the fourth level includes marketing strategy (C04) is the most effective one that acts as the cornerstone of the model and directly affects the third level criteria (content and marketing tools (C03), and marketing performance evaluation (C02)). The first level includes the development of teamwork (C04) as the most effective level. The dimensions of the second level (networking and marketing public relations (C01)) act as interfaces.Extended Abstract                                           IntroductionThe last decade can be considered as the decade of attention to entrepreneurship and entrepreneurs in Iran. Due to the identification of the role and place of entrepreneurship in wealth creation and economic growth, the attention of policy makers and researchers in the field of management has been focused to the identification and understanding of entrepreneurial processes. Entrepreneurship has a meaning beyond the creation of work and employment. In fact, entrepreneurship has other positive and important consequences, such as the flourishing of creativity, encouraging innovation and its development, increasing self-confidence, creating and developing technology, generating wealth in society, and increasing general well-being; and if we just pay attention to its entrepreneurial aspect, we will be deprived of its other consequences (Hoseini et al, 2022). Entrepreneurial marketing is proactively identifying and exploiting opportunities to acquire and retain profitable customers through innovative approaches to managing risk, leveraging resources, and creating value; which includes elements of both concepts: entrepreneurship (activity, risk-taking, opportunity, and innovation), and marketing (customer focus, resource leverage, and value creation). The concept of entrepreneurial marketing focuses on innovations and the development of ideas in line with intuitive understanding of market needs (Gali et al, 2020). Accurate market analysis, identifying and exploiting opportunities, market research, and understanding customer needs are essential elements in entrepreneurial marketing practices. When setting goals, entrepreneurs must consider various factors such as their entrepreneurial goals and marketing strategy, the tactics they will employ, available resources, and the target market. In addition, entrepreneurs should also consider short, medium and long term goals during this process (Mohabattalab & Rezvani, 2018). According to the above, the researcher is looking answer for the following question: What is the model of entrepreneurial marketing based on teamwork with an emphasis on start-up companies?Theoretical FrameworkEntrepreneurial marketingEntrepreneurial marketing is an organizational function and a set of processes to create, communicate and provide value to customers and to manage relationships with customers in ways that benefit the organization and its stakeholders; and characterized with innovation, risk-taking, being active, etc. It may be done without current controlled resources (Nijssen & Mullick, 2023). On the other hand, entrepreneurial marketing is characterized by responsiveness to the market and the apparently intuitive ability to anticipate changes in customer demands (Makhloufi et al, 2022; Opute et al, 2023). Entrepreneurial marketing is a spirit, an orientation, as well as a process for pursuing opportunities and launching and growing ventures that create perceived customer value through relationships, especially through the use of innovation, creativity, sales, market immersion, networking, or flexibility. New companies (startups(There are evidences that state that entrepreneurial marketing is one of the positive characteristics for any organization. Organizations that integrate marketing and entrepreneurial activities are better suited to find and exploit new market opportunities. One of the main advantages of the entrepreneurial marketing concept is its ability to respond to an ever-changing environment. When the entrepreneur is looking for new opportunities with regard to limited resources, he uses an innovative approach in facing this uncertainty (Clark et al, 2022).Team workA team is a limited number of people with complementary skills who are committed to a common goal, the same performance results, and a single approach; who are also responsible for all of these things that they have determined. The teams are connected so that their mission does not end even if only one team member is absent. But in groups, people's personalities are much more independent. It can be said that the concept of team is explained by the word synergy. Synergy happens when people come together to create results that exceed the sum of people's ability (Masumi & Javaherizadeh, 2020).Assarian et al, (2024) investigated the formulation of the native model of social media marketing of online stores. All the indicators obtained from the qualitative analysis of 10 interviews; including 11 categories and the number of 52 indicators, have been used to formulate the native model of social media marketing of online stores. The result of data analysis has been presenting a paradigmatic model including six components of causal conditions (information and communication technology, time management, and cost management), contextual conditions (infrastructure of online stores), intervening conditions (sanctions and economic problems and risk management), strategies (use of force human expert and the use of influencers), the central phenomenon (social media marketing), and consequences (sustainability in the use of social networks, and special value of the brand). A number of indicators were also identified for each of the identified main categories.Moradi ziba et al, (2023) investigated the formulation of digital marketing strategies model in successful Iranian startups. The results of the qualitative part indicated that 241 primary codes, 46 central codes, and 14 selective codes were identified and extracted. The results of the research showed that causal conditions with 4 variables of network capability, use of artificial intelligence, marketing capability, and customer knowledge have an effect on digital marketing strategies, and the results of confirmatory factor analysis showed that the fit indices of the model were confirmed.Research methodologyThe research method is applicable according to its purpose, and qualitative in terms of its implementation. The statistical population consists of 15 experts who are academic professors in the field of marketing management, and managers in the marketing and sales industry, who were selected by targeted non-probability sampling. Research findingsThematic analysis method and MAXQDA software were used for data analysis, and MICMAC software was used for effective and effected between variables. The results showed that 5 comprehensive themes and 13 organized themes and 87 basic codes were identified and extracted from the theme analysis method, and then using interpretative structural modeling, the identified indicators were leveled; and the results showed that the fourth level includes marketing strategy (C04) is the most effective one that acts as the cornerstone of the model and directly affects the third level criteria (content and marketing tools (C03), and marketing performance evaluation (C02)). The first level includes the development of teamwork (C04) as the most effective level. The dimensions of the second level (networking and marketing public relations (C01)) act as interfaces.ConclusionThe current research was conducted with the aim of presenting an entrepreneurial marketing model based on teamwork with an emphasis on start-up companies. The results of the present research are in agreement with the results of Assarian et al, (2024), Moradi ziba et al, (2023), Torres & Jasso (2022), Adeeko & Osunade (2022), Allah Yar (2020), De Groote & Backmann (2020), Amiri (2020), Shabani et al, (2021), Shahramfar et al, (2021), Kordheydari et al, (2019), and Rundquist & Österling (2018). Adeeko & Osunade (2022) showed that the navigation of entrepreneurial marketing education provided through the basic course of entrepreneurship has a significant effect on the entrepreneurial mindset and entrepreneurial skills of students, so it should be sustained.According to the results of the research, the following suggestions are presented:Holding weekly or monthly meetings with the team to review progress, resolve issues, and make joint decisions. Promoting a culture of cooperation and sharing information and experiences within the team. Creating an environment where team members feel converged and learn from each other.Holding team-making events and recreational activities to strengthen personal relationships and motivate team members.Determining the content strategy compatible with the macro marketing strategy. Determining the role of content in attracting customers, keeping them, and promoting products and services.